THE MEMORANDUM OF ASSOCIATION IN THE LIGHT OF THE PROVISIONS ON CONTRACTS OF THE HUNGARIAN CIVIL CODE - Máté, Mohai (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The new Hungarian Civil Code regulates the memorandums of association of companies in its Third Book, while the Sixth Book contains the provisions of (other?) contracts. The memorandum of association is quite different from typical civil law contracts. Its most characteristic feature is that it establishes a legal entity. In most cases, the regulation of the memorandum of association is different from the provisions on contracts set out in the Civil Code, and there is no provision in the law according to which the latter should also be applied to the memorandum of association. But should they?